Claudio Sánchez-Albornoz and the Cuadernos de Historia de España review (1944-1970): A mirror of a life (Estudios de Historia de España, 2019)
In this paper we will deepen in the analysis of the Cuadernos de Historia de España from diferents points of view related to the history of the historiography and the intellectual history, conceiving the review as a privileged observer through which to analyze the life and scientist production of Claudio Sánchez-Albornoz. At the same time, we propose to analyzed differents aspects of his academic network.
Keywords: Spain; History; Historiography; Review; Sánchez Albornoz